Enabling technologies towards personalization of scaffolds for large bone defect regeneration. (April 2022) - Poh, Patrina SP; Lingner, Thomas; Kalkhof, Stefan; Märdian, Sven; Baumbach, Jan; Dondl, Patrick; Duda, Georg N; Checa, Sara
Graphical abstract: Abstract : Additive manufacturing (AM) can deliver personalized scaffolds to support large volume defect tissue regeneration — a major clinical challenge in many medical disciplines. The freedom in scaffold design and composition (biomaterials and biologics) offered by AM yields a plethora of possibilities but is confronted with a heterogenous biological regeneration potential across individuals. A key challenge is to make the right choice for individualized scaffolds that match biology, anatomy, and mechanics of patients. This review provides an overview of state-of-the-art technologies, that is, in silico modelling for scaffold design, omics and bioinformatics to capture patient biology and information technology for data management, that, when combined in a synergistic way with AM, have great potential to make personalized tissue regeneration strategies available to all patients, empowering precision medicine.